ADVERSE DRUG REACTION MONITORING OF FLUCONAZOLE IN A TERTIARY CARE HOSPITAL - .A, Gomathi; M, Sudha.K. (Journal of Biomedical and Pharmaceutical Research, 2020)
Objective: To study the incidence and pattern of adverse effects of Antifungal drug Fluconazole and to assess the severity of its adverse effects. Methodology: The study was approved by Institutional ethics committee and informed consent was obtained from all willing participants. Patients fulfilling inclusion and exclusion criteria were enrolled. Age sex, diagnosis, dose and duration of treatment were recorded. 2ml of blood was collected for liver function test. The adverse drug reaction (ADR) was documented. The causality assessment was done by WHO assessment scale and severity assessment by using modified Hartwig severity assessment scale. Results: In this study, most of the patients were in 31-40 years age group. Among the 100 patients who were on Fluconazole 58 developed adverse drug reactions. 64 percentage of ADRs were reported in patients with treatment duration of more than 12 weeks. The most common adverse drug effect documented was abdominal pain followed by headache. Increase in serum transaminases was noted in 7 percentage of patients who were taking Fluconazole for more than 12 weeks, which did not require treatment termination or dosage alteration. Most of the ADRs were in possible category of causality assessment scale. In severity assessment most of the ADRs were in mild category. Conclusion: Adverse drug reaction to Fluconazole was mostly noted in patients who were on treatment for more than12 weeks of which elevated serum transaminases were observed in 8 patients. Hence regular liver function monitoring is advised in all patients receiving Fluconazole for more than 12 weeks to prevent further liver damage. Keywords: Adverse drug reaction, Fluconazole